The Effect Of The Jigsaw Type Cooperative Learning Model On The Writing Skills Of Grade X Students at SMA Negeri 4 Kediri In Negotiation Text Material For The 2024/2025 Academic Year - Salimatul Ummah, Nur; Muarifin, Moch; Pitoyo, Andri (Jurnal Bahasa Indonesia Prima (BIP), 2025)
This study aims to determine the effect of the Jigsaw learning model on the negotiation text writing skills of tenth-grade students at SMA Negeri 4 Kediri in the 2024/2025 academic year. The research uses a quantitative approach with a quasi-experimental design. The subjects consisted of two classes: a control class that did not use the Jigsaw model and an experimental class that applied the Jigsaw model. The instrument used was a negotiation text writing test. The results showed a clear difference in negotiation writing skills between students who learned using the Jigsaw model and those who did not. The average score in the control class was 70.16, while the experimental class scored 79.44. The hypothesis test produced a significance value of 0.001 (< 0.05), indicating that the Jigsaw model had a positive and significant effect on students’ negotiation text writing skills. These findings confirm that the Jigsaw model is an effective strategy for improving students’ writing abilities.